Gifted students in the educational policy agenda in Mexico (1980-2006) (Foro de Educacion, 2018)
In this paper we analyze educational policies on gifted students (1980-2006), known in Mexico as «estudiantes sobresalientes». The authors point out the way the term «estudiantes sobresalientes» was implemented over the field of Special Education as well as how a political agenda was designed in order to assist gifted childhood and youth. This article also focuses on the design a proposal of an educational intervention. And at the very end how this proposal was developed, the results and the way it was formed as a training program for Mexican Teachers from Public Education. We recognize the fact that the term «estudiante sobresaliente» is ambiguous due to the diversity of student population as well as, in many cases; the gifted status is no visible. We consider the process of selection, assessment and follow up of this project was based on formal concepts and at the same time did not take in consideration the capabilities and skills of the cultural context of each student (community, family and individual). These elements let us understand the educational political agenda (1980-2006) on special education for gifted students as well as the construction of a wide concept of «sobresaliencia» that was design in order to classify and rate them thru that political agenda.